2017
DOI: 10.1071/sh16038
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmissible infection control programs for men who have sex with men – what will they look like in 2020?

Abstract: Abstract. The resurgence of sexually transmissible infections among men who have sex with men is a concern for sexual health. Traditional strategies have relied on the promotion of condom use, regular testing, treatment, and partner management. Future sexually transmissible infection control programs must combine current prevention methods with novel approaches that target the providers, patients, and mechanisms of health care delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…Men who have sex with men (MSM) are disproportionally affected by sexually transmitted infections (STI), such as Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), or syphilis [1][2][3][4][5][6][7]. STI are often asymptomatic, and therefore remaining frequently undetected and untreated [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Men who have sex with men (MSM) are disproportionally affected by sexually transmitted infections (STI), such as Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), or syphilis [1][2][3][4][5][6][7]. STI are often asymptomatic, and therefore remaining frequently undetected and untreated [8].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, HIVpositive (HIV+) MSM often showed higher prevalences of STI than HIV-negative (HIV-) MSM [13,14]. As reasons for higher STI prevalence in MSM in general, higher number of sexual partners as well as higher frequencies of sexual practices with higher risk for acquiring STI are discussed [3,6,7,14]. In Germany, medical guidelines recommend risk adapted STI testing for MSM [15], but costs are not covered by German health insurance if patients do not show STI-related symptoms or if there is no clear report of a substantial risk of infection.…”
Section: Introductionmentioning
confidence: 99%
“…18 Finally, other authors provide recommendations about how to optimise the health of GBM during this period of rapid change and discuss the unintended consequences of getting this wrong. 9–14 Community responses have always underpinned how individual GBM deal with HIV, but government policy provides the social and structural conditions for those community responses to thrive.…”
Section: Introductionmentioning
confidence: 99%
“…3,9 First, clinical services must take full advantage of efficiency offered by the latest technological advances to ensure STI testing becomes as frequent, convenient and as cost-effective as possible. Condoms should be included in the mix of prevention strategies and Crosby argues that they are highly effective when used correctly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation